CONTENT AND LANGUAGE INTEGRATED LEARNING (CLIL) IN TEACHING IT STUDENTS ENGLISH FOR SPECIFIC PURPOSES (ESP) - Tetiana Andriichuk; Ludmyla Lazorenko; Nataliia Doronina (International Journal of Innovative Technologies in Social Science, 2024)
The article is devoted to the study of effective modern methods of planning a practical foreign language lesson for students of IT specialties, the necessity of finding the optimal organization of a practical EFL lesson taking into account the specifics of the IT sphere is shown. The article analyzes the current research of prominent scientists in the field of CLIL (Content and Language Integrated Learning), or subject- and language-integrated learning, which makes it possible to combine learning a foreign language with another academic subject. The advantages of using this methodology in a higher education institution are highlighted on the basis of the author’s own experience. Practical examples of exercises for learning English academic terms, creating presentations, etc. for the effective development of 21st century skills (critical thinking, creativity, teamwork) are given. The key principles of CLIL as an innovative approach to teaching students and the theoretical basis are discussed. Based on Bloom’s Taxonomy, specific key components and words are presented and described in detail to help formulate questions and plan lessons. The tasks that help to develop interesting and meaningful classes for IT students in higher education, which will be in demand in the labor market in the future, are detailed.